2017
DOI: 10.1089/ten.tea.2016.0494
|View full text |Cite
|
Sign up to set email alerts
|

NANOG Restores Contractility of Mesenchymal Stem Cell-Based Senescent Microtissues

Abstract: Mesenchymal stem cells (MSCs) have been extensively used in the field of tissue engineering as a source of smooth muscle cells (SMCs). However, recent studies showed deficits in the contractile function of SMCs derived from senescent MSCs and there are no available strategies to restore the contractile function that is impaired due to cellular or organismal senescence. In this study, we developed a tetracycline-regulatable system and employed micropost tissue arrays to evaluate the effects of the embryonic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…We have previously demonstrated that the pluripotent factor NANOG was sufficient to reverse cellular aging and to completely restore the diminished differentiation capacity of aged MSCs and the contractile function of MSC-derived SMCs (1,2,18,19). Here, we report that NANOG also restored the effects of aging on collagen production in both senescent MSCs and HGPS-derived myofibroblasts as shown in traditional cultures and 3-dimensional vascular tissue mimetics.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We have previously demonstrated that the pluripotent factor NANOG was sufficient to reverse cellular aging and to completely restore the diminished differentiation capacity of aged MSCs and the contractile function of MSC-derived SMCs (1,2,18,19). Here, we report that NANOG also restored the effects of aging on collagen production in both senescent MSCs and HGPS-derived myofibroblasts as shown in traditional cultures and 3-dimensional vascular tissue mimetics.…”
Section: Discussionsupporting
confidence: 55%
“…We also discovered that ectopic expression of the pluripotent factor NANOG (Nanog homeobox) was sufficient to reverse cellular aging and restore the diminished contractile capacity of aged myogenic progenitors using 3 different models of aging: 1) organismal aging; 2) replicative senescence; and 3) Hutchinson-Gilford progeria syndrome (HGPS) or premature aging (18). In addition, we reported that NANOG restored ACTIN polymerization, and induced myocardinrelated transcription factor A (MRTF-A) translocation to the nucleus and serum response factor (SRF)-dependent myogenic gene expression (18), ultimately restoring the force generation ability of senescent MSCs and HGPS cells (19). Here we report that NANOG also reversed the impaired production of COL3 in senescent MSCs and HGPS cells by reactivating the impaired TGF-b1 pathway through transcriptional control of several genes, including mothers against decapentaplegic (SMAD)2 and SMAD3.…”
mentioning
confidence: 99%
“…Administration of rapamycin, an inhibitor of the mTOR signaling pathway, raised the expression level of NANOG, postponed replicative arrest, and enhanced the lifespan increment of BM-MSCs[ 116 ]. NANOG, an embryonic transcription factor, is a pluripotency marker that facilitates myogenic differentiation and restores the contractile function of senescent MSCs[ 117 ]. Additionally, a high number of potential regulators involved in senescent MSC rejuvenation have been screened and investigated in vitro .…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…In particular, the pluripotency factor NANOG is essential for maintaining the self-renewal of ESCs over many population doublings (19). Although overexpression of NANOG does not confer pluripotency to somatic cells, it has been shown to restore several cellular functions that are compromised by aging including proliferation and differentiation of senescent fibroblasts and mesenchymal stem cells (20)(21)(22). In vivo endogenous expression of this transcription factor in stratified epithelia of adult mice showed that systemic overexpression of NANOG induces hyperplasia without initiating tumors (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%